2010
DOI: 10.1089/dia.2009.0171
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Veterans Administration Use on Indicators of Diabetes Care in a National Sample of Veterans

Abstract: Background: Diabetes poses a serious health burden, of which veterans have a disproportionate share. Few data exist regarding differences in self-care behaviors and provider-based quality of care indicators among a large sample of veterans. The objective of this study was to determine the effect of Veterans Affairs (VA) use on diabetes quality of care indicators among veterans. Methods: A cross-sectional analysis was done on data from 36,525 veterans in the 2003 Behavioral Risk Factor Surveillance Survey. VA u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Previous studies have demonstrated that the VHA is often better than non-VHA settings at achieving highquality care, across disciplines and settings. [33][34][35][36][37] H pylori retesting has not been explicitly compared in VHA and non-VHA systems, but should not vary significantly from other quality care metrics. Still, future studies should validate our findings in other large, non-VHA settings.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the VHA is often better than non-VHA settings at achieving highquality care, across disciplines and settings. [33][34][35][36][37] H pylori retesting has not been explicitly compared in VHA and non-VHA systems, but should not vary significantly from other quality care metrics. Still, future studies should validate our findings in other large, non-VHA settings.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, diabetes care in the VA system has improved substantially over time, attributed to increased use and dissemination of performance measures, clinical reminders, and data tracking. [28][29][30] The study was conducted during a period of system-wide declines in A1c. These possibilities would bias the study in favor of similar improvement across groups and in favor of the null hypothesis of no differences between groups.…”
Section: Discussionmentioning
confidence: 99%
“…51 Receipt of diabetes education and annual HbA1c tests was higher among VA patients compared with veterans in non-VA care. 52 VA patients were more likely than veterans receiving care outside VA to receive recommended diabetes care, including being twice as likely to have a foot examination and 60-70 % more likely to have an eye examination, two or more A1c tests, and two or more providers visits, 53 a routine checkup within 2 years (91.6 % among VA patients compared to 80.6 % overall; P < 0.001), 54 and influenza and pneumonia vaccinations (rates increased 10-240 %), 53,55,56 but similar rates of cholesterol screening. 55 Blood pressure control was higher among male African-American VA patients than male African-American non-VA patients (49.4 % vs. 44.0 %, P < 0.01) though similar among Caucasians.…”
Section: Safetymentioning
confidence: 99%